Anti-programmed death-1 inhibitors and nimotuzumab in combination with induction chemotherapy for locoregionally advanced nasopharyngeal carcinoma: a propensity score-matched analysis - Ya-Ni Zhang; Yu-Pei Chen; Pu-Yun OuYang; Tai-Xiang Lu; Fang-Yun Xie; Fei Han; Chun-Yan Chen (Therapeutic Advances in Medical Oncology)
Background: The poor prognosis of locoregionally advanced nasopharyngeal carcinoma (LANPC) due to the high incidence of metastasis necessitates effective treatment strategies. Synergistic effects have been observed when anti-programmed death-1 (PD-1) inhibitors are combined with chemotherapy or targeted therapy. Objectives: To compare the efficacy and safety of induction chemotherapy in combination with nimotuzumab with or without anti-PD-1 inhibitors for LANPC. Design: Retrospective study. Methods: In total, 319 patients with LANPC were retrospectively enrolled between December 2017 and November 2022. The primary endpoint was progression-free survival (PFS). Propensity score matching was performed to adjust for potential confounders. Results: Overall, 150 patients were included after propensity score matching. The immunotherapy + nimotuzumab + chemotherapy (INC) group ( n  = 50) had a higher 3-year PFS rate (96.6% (95% confidence interval (CI): 93.2–100.0)) than the nimotuzumab + chemotherapy (NC) group ( n  = 100) (79.8% (95% CI: 75.6–84.0)). The INC group had a hazard ratio of 0.16 (95% CI: 0.02–1.22; p  = 0.04). The objective response rates were 100% and 99% for the INC and NC groups, respectively. Grade ⩾3 treatment-related adverse events were reported in eight (5.3%) patients, and hyponatremia (2.0%) was the most common. Grade ⩾3 immune-related adverse events (rash and reactive capillary proliferation) were reported in two (4.0%) patients. Conclusion: INC demonstrated remarkable anti-tumor activity with acceptable safety for LANPC.